2019
DOI: 10.7567/1347-4065/ab0279
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structural and photoluminescence properties of Mg2Si/Si nanocomposites consisting of Si nanosheet bundles and Mg2Si deposits

Abstract: Mg2Si/Si nanocomposites, consisting of Si nanosheet bundles and Mg2Si deposits formed on the Si nanosheet bundles, were formed by the thermal annealing of CaSi2 powders in MgCl2 vapor. Mg atoms are deposited on the Si nanosheet bundles, and the surface of the nanosheets were partially transformed into the Mg2Si phase during the thermal treatment. The Mg2Si/Si composites were also synthesized on Si(111) substrates. The structural and photoluminescence (PL) properties of the composites were characterized. The Mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…It should be noted that in a previous study, a new emission peak at approximately 1.9-2.0 eV appeared for a Mg 2 Si composite. 19) Thus, it is considered that the P3 emission peak is related to Mg 2 Si. RT visible luminescence at 1.97 and 2.14 eV in Mg 2 Si:Al films has also been observed, and it was concluded that the emissions arise from transitions related to interfacial oxide defects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that in a previous study, a new emission peak at approximately 1.9-2.0 eV appeared for a Mg 2 Si composite. 19) Thus, it is considered that the P3 emission peak is related to Mg 2 Si. RT visible luminescence at 1.97 and 2.14 eV in Mg 2 Si:Al films has also been observed, and it was concluded that the emissions arise from transitions related to interfacial oxide defects.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, powder forms of Mg 2 Si/Si composites were synthesized, and their structural and optical properties were characterized. 19) Recently, the synthesis of Mg 2 Si nanosheets via Ca atom extraction from CaSi 2 microwalls followed by the incorporation of Mg into the microwalls on Si substrates via thermal annealing in a MgCl 2 /Mg mixed vapor has been reported, and the structural and PL properties of the bundles were characterized. 20) In this study, the detailed structural property of the Mg 2 Si nanosheet bundles was elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…25) Mg 2 Si/Si nanocomposites comprising Si nanosheet bundles and Mg 2 Si deposits have been synthesized; however, homogeneous single-phase Mg 2 Si nanosheets have not been formed using MgCl 2 , which was carefully stored to avoid deliquescence. 26) The Mg 2 Si nanosheet bundles were synthesized by annealing in MgCl 2 /Mg mixed vapor. 27) An additional Mg source was required to form homogeneous single-phase Mg 2 Si nanosheet bundles.…”
Section: Discussionmentioning
confidence: 99%
“…6), 13) Additionally, Mg 2 Si/Si composites containing Si nanosheet bundles and Mg 2 Si deposits were synthesized via heating treatment CaSi 2 and MgCl 2 mixture in a sealed stainless-steel cell under Ar atmosphere at 650 °C. 14) The prepared Mg 2 Si/Si composites affect the emission property of the Si nanosheets. 14) Therefore, the reaction of CaSi 2 and transition metal chlorides mixture is an effective method to acquire various Si-based nanosheets or nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…14) The prepared Mg 2 Si/Si composites affect the emission property of the Si nanosheets. 14) Therefore, the reaction of CaSi 2 and transition metal chlorides mixture is an effective method to acquire various Si-based nanosheets or nanocomposites.…”
Section: Introductionmentioning
confidence: 99%